How Goal Free Problems Affect for Students with Learning Experiences? - Damianus Dao Samo; Irna Karlina Sensiana Blegur; Wara Sabon Dominikus; Siprianus Suban Garak; Juliana Mehelina Herlince Nenohai; Yohanes Hariaman Nada (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This brief research aims to see whether there are significant changes in higher order thinking skills and cognitive load of students who have learning experiences, before and after being exposed to the goal free problems approach. This quasi-experimental research used the One-Group Pre-test Post-Test Design which carried out through four phases: prior knowledge activation phase; pre-test phase; acquisition phase and post-test phase. There were 33 students (average age 19.27 years) who were actively involved. The results confirmed the hypothesis where: 1) There is a significant difference (p = 0,00) between the average higher order thinking skills of students before learning through the goal free problems approach (X = 45.14, SE = 4.12) and the average higher order thinking skills of students after learning through the goal free problems approach (X = 61.52, SE = 4.03); and 2). There is a significant difference (X = 8.44, SE = 0.13) between the average cognitive load of students before learning through the goal free problems approach (X= 4.64, SE= 0.34) and the average cognitive load of students after learning through the goal free problems (X= 4.65, SE= 0.34).